PELAKSANAAN PERLINDUNGAN TENAGA KERJA ANAK DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DIHUBUNGKAN DENGAN PASAL 28B AYAT (2) UNDANG- UNDANG DASAR 1945 - Evariana, Dian (LPPM Universitas Bina Bangsa, 2023)
The entry of children in the work area then initiated the government to make specific regulations as stated in Law Number 13 of 2003 concerning Manpower. In this Law, the issue of child labor is in articles 68-75, all of which are essentially efforts to protect against the work system that harms the physical and mental development of children. This condition is sufficient to provide reasons for the compiler to conduct scientific research related to child employment behavior in conjunction with Law Number 13 of 2003. More specifically, the compiler tried to analyze Articles 68-75 which contain regulations on child employment. The purpose of this study is to find out how the regulations regarding the protection of child labor in Serang City, to find out how the implementation of articles 68-75 of Law number 13 of 2003 concerning Manpower is related to article 28 b of the 1945 Constitution concerning the protection of child labor in Serang City and to find out how the efforts made by the government in protecting child labor in Serang City. The research method used by the compiler is analysis because this research is qualitative based on various library sources and other documents relevant to the research material. The summary of the results of this study is that special protection for children is based on the reality that children are rudimentary human beings physically and mentally. This behavior is for example by recruiting children at a young realistic age, inadequate wages, excessive working time and no special protection in the process of child labor